Game Edu IT: Combining Technology Literacy with an Interactive Approach - Fortilla, Zeny Arsya; Al-Ghazali, Taufiq Akbar (Department of Informatics Faculty of Engineering Universitas Malikussaleh, 2025)
This study aims to integrate technology literacy into the learning process through an interactive approach packaged as an educational game application developed using Scratch. The game is designed with a question-and-answer system to stimulate players' awareness of their abilities and enhance their curiosity about technology. Players will earn points as rewards for successfully answering questions posed by the game's characters, offering both engaging entertainment and educational value. Through